Effect of sun-dry on nutritional and sensory acceptability of wilted African leafy vegetables: a case study of Morogoro Region, Tanzania - Ahmed, Amina; Almas, Saliath; Kissaka, Kelvin; Suleiman, Rashid (Frontiers in Sustainable Food Systems, 2023)
African leafy vegetables are rich in micronutrients that can help solve hidden hunger problems in Sub-Saharan Africa. However, their availability is limited due to seasonality and high post-harvest losses, which account for about 50%. In the field survey, we observed that wilted vegetables are usually discarded from the Morogoro region, Tanzania markets. That loss also contributes to the loss of resources used to cultivate and transport the vegetables. Therefore, this study aimed to investigate the effect of the commonly used sun-drying method on the nutritional and sensory properties of fresh and wilted African nightshade and cowpea leaves. The common practice of handling fresh vegetables by vendors was adopted by putting the freshly harvested vegetables in an open basin at 24 ± 2˚C for three days. Then, the stored vegetables were either sprayed or dipped in water to reduce the wilting rate. Next, the fresh and the wilted vegetables were dipped into hot water at 100°C for 7 min. Afterwards, the vegetables were sundried (22.5 ± 5.5˚C) for three consecutive days. To study the effect of wilting, blanching, and sun drying, fresh and dried vegetables were analysed for moisture, ascorbic acid, β-carotene, antioxidant activity and nitrate contents. Fresh and dried vegetables were used to prepare sauces using traditional recipes. The vegetable sauces were analysed for their sensory attributes using 30 semi-trained panellists. After drying, ascorbic acid contents, antioxidant activity and nitrate were reduced. The β-carotene significantly increased in the nightshade while decreasing in the cowpea leaves. Ascorbic acid ranged from 17.40 to 2.22 mg/100g, antioxidant activity from 37.30 to 19.78, nitrate 230 to 10 mg/100g and β-carotene from 96.38 to 79.49 mg/100. The sensory results showed relative acceptability among the sauces prepared from the fresh, fresh-dried and wilted-dried vegetables. In conclusion, blanching before drying reduced the water-soluble nutrient content but improved the sauces' sensory scores of fresh and wilted vegetables. Therefore, reducing the post-harvest loss of African leafy vegetables is possible by drying the wilted vegetables and preparing the sauces with acceptable quality.